2022
DOI: 10.1002/cptc.202200098
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Intersystem Crossing by Chemical Composition and Solvent Effects: Benzophenone, Anthrone and Fluorenone

Abstract: Combined density functional theory and multireference configuration interaction methods including spin‐orbit coupling and spin‐vibronic interactions have been used to elucidate the photophysical pathways of benzophenone (BP), anthrone (A) and fluorenone (FL). Our results reveal that the slower S1(1nπ*) T1(3ππ*) passage of FL in the gas phase, as compared to BP and A, originates from the different electronic structures of the T1(3ππ*) states in these compounds and is not related to the planarity of the nuclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…For example, benzophenone has been reported to undergo ISC on the picosecond time scale with near unity efficiency [36–39] . Such a quantitative ISC is observed in thioxanthone, [21,32] acetophenone, [22,40–43] anthrone, etc., [28] as well. Not only the type of aromatic keto but also the environment, such as solvent polarity, [44,45] temperature, [46] and pressure [47] assists in modulating ISC [13] …”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…For example, benzophenone has been reported to undergo ISC on the picosecond time scale with near unity efficiency [36–39] . Such a quantitative ISC is observed in thioxanthone, [21,32] acetophenone, [22,40–43] anthrone, etc., [28] as well. Not only the type of aromatic keto but also the environment, such as solvent polarity, [44,45] temperature, [46] and pressure [47] assists in modulating ISC [13] …”
Section: Introductionmentioning
confidence: 94%
“…Notably, aromatic ketones are well known for their rapid and efficient intersystem crossing (ISC) [11,21,22,28–32] . The lone pair orbital of the carbonyl group contributes to the n‐orbital.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most widely studied examples of ISC dynamics in heavy metal free organic molecules is benzophenone, which exhibits ISC in the picosecond regime. Excited state dynamics simulations of benzophenone performed by Favero et al demonstrated that direct (i.e., S 1 → T 1 ) ISC accounted for the majority of the spin-flipping dynamics, with the remaining crossing to the T 2 or higher triplet states, which subsequently undergo ultrafast nonradiative decay into the T 1 state. Their simulations ascribed the fast ISC to two internal coordinates activated after n –π* excitation, namely, the CO stretch and the torsion of phenyl rings.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23][24][25][26][27] Notably, aromatic ketones are well known for their rapid and efficient intersystem crossing (ISC). [11,21,22,[28][29][30][31][32] The lone pair orbital of the carbonyl group contributes to the norbital. Meanwhile, carbonyl and aromatic rings define the π-orbital.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, aromatic ketones are well known for their rapid and efficient intersystem crossing (ISC) [11,21,22,28–32] . The lone pair orbital of the carbonyl group contributes to the n‐orbital.…”
Section: Introductionmentioning
confidence: 99%